The killing touch - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
In Dschang, Cameroon, a simple technique for controlling weeds that are difficult to eradicate in tropical conditions has been developed. The `'magic glove' system consists of a plastic glove with a piece of foam stuck to it which is wetted all the...